The Application of Nanoscale Zero-Valent Iron Promotes Soil Remediation While Negatively Affecting Soil Microbial Biomass and Activity - Anza, Mikel; Salazar, Oihane; Epelde, Lur; Alkorta, Itziar; Garbisu, Carlos (Frontiers in Environmental Science, 2019)
The use of nanoscale zero-valent iron particles (nZVI) for soil remediation is gaining increased attention. However, there are concerns about the potential adverse effects of nZVI on soil microbial communities and, hence, soil quality. The objective of this study was to assess the impact of the application of nZVI on soil microbial parameters (as bioindicators of soil quality) during the nanoremediation of a soil artificially contaminated with lindane (10 mg γ-HCH kg-1 DW soil) and zinc (1,500 mg Zn kg-1 DW soil). nZVI were also applied to non-contaminated soil. The following nZVI doses were applied twice: 0, 0.25, 0.5, 1 and 2 mg nZVI g-1 DW soil. Nine weeks after nZVI application, the following parameters were determined in soil samples: lindane concentration, extractable Zn concentration, microbial biomass carbon (CMB), bacterial and fungal abundance (gene copy numbers by qPCR), enzyme activities (β-glucosidase, β-glucosaminidase, xylosidase, acid phosphatase, arylsulphatase and Leu-aminopeptidase) and bacterial richness by ARISA profiles. The application of nZVI reduced lindane and extractable Zn concentrations following a dose-dependent pattern. The presence of contaminants reduced soil microbial biomass and activity. The application of nZVI negatively affected the microbial quality of the contaminated soil but not of the non-contaminated soil. This observation might reflect a “stress-on-stress” effect, i.e. the already stressed microbial populations present in the contaminated soil were more sensitive to the application of nZVI (a second stress) than those present in the non-contaminated soil.